Brüssel, Frankfurt oder Basel: Wo muss das Problem steigender Staatsschulden in der Europäischen Währungsunion gelöst werden? - Philipp Paulus (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2006)
– This paper shows that in addition to fiscal rules in the European Monetary Union (EMU), some support can be found from financial markets to keep rising public debt in check. EMU likely has an overall positive impact on the ability of both markets and market participants for EMU government bonds to price such securities correctly, which would in turn discipline profligate EMU governments. However, apart from fiscal rules like the Stability and Growth Pact, some regulatory issues will still have to be addressed to ascertain the functioning of markets for EMU government bonds. It is concluded that regulatory efforts should concentrate on competition policy by the EU Commission in Brussels for EMU financial markets and banks, as well as on an EMU-wide authority for the ECB in Frankfurt to monitor and combat systemic risk. However, the Basel accords on capital requirements for banks should not be made legally binding, since leaving risk-taking and risk measurement to banks individually likely helps overcome competitive distortions in a larger EMU capital market.
Keywords: F33; G28; H63; 330; monetary union; fiscal stability; banking system; banking regulation